FENOMENA GAME MOBILE LEGENDS BAGI PEREMPUAN ANGGOTA VICTORY SQUAD - Ike Ireztyawan; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Mobile Legends Game is an online game is an online game that phenomenon in all major cities in Indonesia including in Pekanbaru city. The enthusiasts of Mobile Legends games ranging from children, adolescents to adults. Interestingly, the phenomenon of Mobile Legends game is also happening to women. There is only one women only squad that is Victory Squad. Victory Squad has 8 female members who play this Mobile Legends game almost every day. Mobile Legends Game is a game action strategy that requires cohesiveness, but often found in this Mobile Legends game users who use harsh words. This research is to know the motive, meaning and experience of female communications member of Victory Squad in playing Mobile Legends game.This research uses qualitative research method with phenomenology approach. The subjects consisted of 5 members of Victory Squad who were selected using Purposive Sampiling technique. This study uses in-depth interview data collection, observation, and research documentation. To achieve the validity of the data in this study, researchers used extension of participation and triangulation.The results show first, the female motives of Victory Squad members to play Mobile Legends game consists of motives because (because motive) that is hobby, trend, social environment, and fad. While the motive for (in order to motive) that is popularity and not underestimated. Second, the meaning given by women members of Victory Squad to Mobile Legends game that is game as means and game as world. Third, the Victory Squad women's communication experience is categorized into two pleasant communication experiences and an unpleasant communication experience. Both categories are a communication experience of women Victory Squad members with family, with one team in the Mobile Legends game and with the environment. The form of a fun communication experience in this case is the support and acceptance of the family, the existence of solidarity and mutual support in the game game Mobile Legends game, as well as the support and acceptance of the surrounding environment like friends. While the form of communication experience is not fun is the prohibition and rejection of the family, the presence of players who are selfish, not compact and said rough or dirty in a team game Mobile Legends game, and the existence of a rejection or a negative view of women who play Mobile Legends games from the surrounding environment .Keyword: Phenomena, Game Mobile Legends , Phenomenology, Victory Squad Members